Dynamical Behavior of the Charge Transfer Phase Transition in Dithiooxalato-Bridged Iron Mixed-Valence System - Enomoto, Masaya; Watanabe, Isao; Kojima, Norimichi (Current Inorganic Chemistry (Discontinued), 2016)
Objective: We review the dynamical behavior of the charge transfer phase transition in aniron mixed valence system, (CnH2n+1)4N[FeIIFeIII(dto)3] (dto = C2O2S2). Background: In the case of assembled metal complex systems whose spin states are situated in the spin crossover region, synergetic phenomena coupled with spin and charge have been expected. Based on this viewpoint, we have developed a ferromagnetic organic-inorganic hybrid system, (CnH2n+1)4N[MIIFeIII(dto)3], and discovered the charge transferphase transition (CTPT), where the thermally induced electron transfer between FeII and FeIII occurs reversibly. However, the dynamics of the CTPT has not well been elucidated by the measurements of magnetic susceptibility, EPR and 57Fe Mössbauer spectroscopy. Methods: In order to investigate the dynamics of CTPT for (CnH2n+1)4N[MIIFeIII(dto)3], we performed muon spin relaxation spectroscopy at Rutherford-Appleton Laboratory (UK) and the Paul Scherrer Institut (Switzerland), and dielectric constant measurement. Results: From the analysis of muon spin relaxation, we revealed the hopping rate of electrons between the FeII and FeIII sites at the CTPT. Moreover, we observed an anomalous enhancement of dielectric constant due to the valence fluctuation at the CTPT. This anomaly has a tendency to be divergent as the measuring frequency is lowered to 1 Hz, which is quite similar to the dielectric relaxation in relaxor ferroelectrics. Conclusion: In a mixed-valence system, (CnH2n+1)4N[MIIFeIII(dto)3]], we have investigated the CTPT due to the synergetic effect coupled with spin and charge, and revealed the valence fluctuation at the CTPT by means of muon spin relaxation spectroscopy, and dielectric constant measurement techniques.
Keywords: ferromagnetism